Choroidal spatial distribution indexes as novel parameters for topographic features of the choroid - Hwang, Sungsoon (Sci Rep, 2020)
The purpose of the study is to propose choroidal spatial distribution indexes (CSDIs) to represent choroidal topographic features, establish a normative database for CSDIs, and identify factors associated with CSDIs in healthy eyes. Retrospective data analysis of 363 healthy eyes from a single-center, prospective, cross-sectional, non-interventional study. Subjects were evaluated using spectral domain OCT with enhanced depth imaging. Choroidal volume and average thickness were measured with OCT in nine macular subfields defined by the Early Treatment Diabetic Retinopathy Study. Vertical CSDI was defined as the natural logarithm of superior choroidal volume divided by inferior choroidal volume. Horizontal CSDI was defined as the natural logarithm of temporal choroidal volume divided by nasal choroidal volume. The overall distributions of vertical and horizontal CSDIs was analyzed. Linear regression analyses were used to identify ocular and systemic factors associated with vertical and horizontal CSDIs. The average vertical CSDI was 0.062 ± 0.206, and average horizontal CSDI was 0.138 ± 0.226. Both vertical and horizontal CSDIs followed normal distribution. Increasing age was significantly associated with greater vertical CSDI (choroidal volume distribution tilted toward the superior region), and longer axial length and thinner subfoveal choroidal thickness were significantly associated with greater horizontal CSDI (choroidal volume distribution tilted toward the temporal region).